The dynamic genomes of Salvinia reshape our understanding of fern chromosome evolution - Yanã C. Rizzieri; Ponpipat Limpanasittichai; Fernando Hernández; Jonas I. Mendez-Reneau; Stacy D. Holt; Brittany Sutherland; Terezie Mandáková; James B. Beck; Li-Yaung Kuo; Nicholas J. Kooyers; Fay-Wei Li; Erin M. Sigel (Proceedings of the National Academy of Sciences, 2026)
Ferns are well known for their exceptionally large genomes and high chromosome numbers, which may be in part due to whole genome duplications (WGDs) followed by slow diploidization. To better understand the mode of fern genome evolution, we focus on the heterosporous fern genus Salvinia, which exhibits striking variation in genome size and chromosome number. We generated chromosome-level genome assemblies for Salvinia cucullata, the fern with the smallest genome, and Salvinia molesta, a globally invasive species widely thought to be an allopentaploid. Surprisingly, we found that S. molesta is in fact a diploid hybrid and that S. cucullata , despite having a genome ten times smaller than S. molesta , has substantially more chromosomes. Both species lack any recent WGDs and their highly variable genomes were predominately shaped by transposable element proliferation and chromosome rearrangements. The complete decoupling of chromosome number and genome size in Salvinia sharply contrasts the typical pattern in ferns, which are mostly homosporous and produce only one type of spore by meiosis. Many of the genome features observed in Salvinia are consistent with genomic changes due to female meiotic drive, a mechanism possible only in heterosporous plants that produce distinct microspores and megaspores. These results redefine the genetic identity of S. molesta and provide insights into its invasive success. The marked variation in genome composition and structure within Salvinia challenges the prevailing model of fern genome evolution while aligning with expectations for angiosperms, another heterosporous lineage.